2017
DOI: 10.1002/acm2.12146
|View full text |Cite
|
Sign up to set email alerts
|

AAPMRSS Medical Physics Practice Guideline 9.a. for SRSSBRT

Abstract: The American Association of Physicists in Medicine (AAPM) is a nonprofit professional society whose primary purposes are to advance the science, education, and professional practice of medical physics. The AAPM has more than 8,000 members and is the principal organization of medical physicists in the United States.The AAPM will periodically define new practice guidelines for medical physics practice to help advance the science of medical physics and to improve the quality of service to patients throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 28 publications
5
55
0
Order By: Relevance
“…Equipment MME v1.5 was commissioned on an Elekta VersaHD linac with two high-dose-rate flattening filter-free (FFF) and two flattened photon modes. The models were validated, and a comprehensive quality assurance process was established according to the recommendations of the American Association of Physicists in Medicine Practice Guidelines 5.a, 8.a, and 9.a [11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…Equipment MME v1.5 was commissioned on an Elekta VersaHD linac with two high-dose-rate flattening filter-free (FFF) and two flattened photon modes. The models were validated, and a comprehensive quality assurance process was established according to the recommendations of the American Association of Physicists in Medicine Practice Guidelines 5.a, 8.a, and 9.a [11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…In general, the effective radiation dose in a year in patients with VUR at our institution was approximately 5.5 mSv/year with the additional natural background radiation sources, including radon, cosmic rays, terrestrial, and internal sources, that results in an effective dose of approximately 620 millirems (6.2 mSv) according to the American Association of Physicists in Medicine (AAPM). 13…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that the beam-positioning error was within 0.92 mm with a couch angle of 0.5 • at a range of 0 to 5.0 cm distance from the isocenter and confirmed that the accuracy was within 1.0 mm as recommended by the AAPM-RSS. 14 Based on various perspectives regarding the effect of rotational errors on dose distribution for the target and beam-positioning accuracy, rotational errors should be detected and corrected using an imageguided radiotherapy technique. Tsuruta et al evaluated the correlation between intrafractional residual setup errors and the accumulation of delivered dose distributions in 72 consecutive patients with multiple brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on beam-positioning accuracy, the AAPM and Radiosurgery Society (RSS) recommend that the accuracy should be within 1.0 mm for SRS and stereotactic body radiation therapy (SBRT). 14 The beam-positioning accuracy is typically evaluated at the isocenter position; however, it is also necessary to confirm the beam-positioning accuracy at off -isocenter positions. 12,15 To evaluate the beam-positioning accuracy at off -isocenter positions, Gao et al performed an off -isocenter Winston-Lutz (WL) test for SRS and SBRT.…”
Section: Introductionmentioning
confidence: 99%